"I've had horrible things said about me": An inductive content analysis of nursing academic experiences of contra-power harassment from undergraduate nursing students. (July 2021) - Christensen, Martin; Craft, Judy; White, Sara
Abstract: Aim: The aim of this study was to describe the experiences of nursing academics exposure to contra-power harassment by under-graduate nursing students. Background: Contra-power harassment by nursing students is a growing phenomenon which is defined as the harassment of those ni formal positions of power by those who are not. Harassing behaviours can include verbal, physical and sexual and digital harassment through mediums such as social media. Cited behaviours perpetrated by under-graduate nursing students are often experienced after the release of grades. Design: A self-administered online questionnaire was used to elicit responses to four open-ended questions regarding nursing academics experiences of contra-power harassment and nursing student incivility. Method: Inductive content analysis was used to identify text patterns from the academic comments. Each of comments was read through to get a sense of the whole. Re-reading the comments allowed for open coding into broad headings which described a specified meaning. Categorising the broad headings into higher order sub-categories then made it permissible to record comments that belonged to a particular group. The development of the main category using abstraction was first undertaken by creating generic categories from the sub-categories using content-characteristic words. The development of the broad and sub-categories were assessed independently by two of the authors and after discussion, agreement was reached as to the structure of the generic categories. Results: A total of 159 comments received from 82 nursing academics each describing incidents of contra-power harassment. Nursing academics were faced with several differing behaviours that were seen as aggressive, anger, manipulation and threats. These were viewed as both verbal and isolation attacks In all, four generic categories were identified – Experiencing Harassment; You're Adding to My Stress; Being Set-up to Fail; Feeling Unsafe Professionally and Academically. Nursing academics describe experiencing the behaviours of contra-power harassment as being distressing, disturbing, frustrating, saddening and disappointing. Conclusion: The behaviours expressed by nursing students tended to occur at the release of grades. Most academics were concerned for their own safety both emotionally and physically because of the unpredictability of student behaviour. Most academics understood the pressures nursing students faced, especially the international students. However, they were often challenged by the need to support student learning and maintaining professional standards of behaviour. Highlights: There is increasing concern of incivility perpetrated by nursing students against academics. It is at the release of grades that the most nursing student incivility occurs. Most academics felt threatened both physically and emotionally at the hands of nursing students. Some nursing academics feel unsupported by university management when dealing nursing student incivility. Consumerism and self-entitlement were seen as significant contributing factors to behaviours experienced.